2014
DOI: 10.1002/ajmg.a.36649
|View full text |Cite
|
Sign up to set email alerts
|

Are 22q11.2 distal deletions associated with math difficulties?

Abstract: Approximately 6% of school-aged children have math difficulties (MD). A neurogenetic etiology has been suggested due to the presence of MD in some genetic syndromes such as 22q11.2DS. However, the contribution of 22q11.2DS to the MD phenotype has not yet been investigated. This is the first population-based study measuring the frequency of 22q11.2DS among school children with MD. Children (1,564) were identified in the schools through a screening test for language and math. Of these children, 152 (82 with MD a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 38 publications
1
27
0
1
Order By: Relevance
“…A phenotype is emerging for deletion of the D–E segment (Carvalho et al. 2014; Mikhail et al. 2014), but other abnormalities are relatively rare and information is lacking.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A phenotype is emerging for deletion of the D–E segment (Carvalho et al. 2014; Mikhail et al. 2014), but other abnormalities are relatively rare and information is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Carvalho et al. (2014) have presented a recent literature review of all patients with this deletion with the exception of the six cases reported by Mikhail et al. (2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations